Comparison of Three Different New Bipolar Energy Modalities and Classic Bipolar in Vivo for Tissue Thermal Spread - Melike Demir ÇALTEKİN; Serpil AYDOĞMUŞ; Serenat Eriş YALÇIN; Emine DEMİREL; Fulya CAKALAĞAOĞLU UNAY; Pelin ÖZÜN ÖZBAY; Aslı Deniz CEYHAN ÖZDEMİR; Yakup YALÇIN; Sefa KELEKÇİ (Federation of Turkish Pathology Societies, 2017)
Objective: The aim of this study was to compare three different new bipolar energy modalities and classic bipolar in vivo for tissue thermal spread. Material and Method: This prospective, randomized, single-blind study was conducted between Septemsber 2012 and July 2013. Eighteen patients aged 40-65 years undergoing hysterectomy and bilateral salpingectomy for benign etiology were included in the study. Before the hysterectomy operation began, it was marked nearly distal third cm started from uterine corn and proximal close third cm started from fimbrial bottoms by visualizing both fallopian tubes. The surgery was performed using one 5 mm applicator of PlasmaKinetics™, EnSeal®, LigaSure™ or classic bipolar energy modality. The time each device was used was standardized as the minimum time of the audible warning of the device for tissue impedance and as tissue vaporization on classic bipolar. Tissues were dyed by both H&E and Masson's Trichrome in the pathology laboratory. Thermal spread was compared. Results: Evaluation of the damage on the uterine tubes by each device used revealed that LigaSure™ was associated with increased thermal injury compared to PlasmaKinetics™ (p=0.007). Apart from PlasmaKineticsTM (p=0.022), there was no statistically significant difference between the three devices in terms of thermal damage spread in the distal and proximal fallopian tubes. Conclusion: To reduce lateral thermal damage, Plasmakinetics™ may be preferable to Ligasure™ among the three different new bipolar energy modalities.